Lateral Earth Pressure Analysis for Cantilever wall and Mechanically Stabilised Earth wall Optimisation: A Numerical Study - Mustapah, Nur Iman Elianie; Chee Ming Chan; Salina Sani (Progress in Engineering Application and Technology, 2024)
The construction of infrastructure on elevated ground requires the development of earth embankments. Ensuring these embankments are stable and sustainable is crucial to prevent excessive land use and reduce costs. Retaining walls are essential for maintaining the stability and safety of these structures. This research focuses on the necessity of retaining walls to resist sudden soil movements and maintain stability. Using Plaxis 2D, a finite element analysis software, the study aims to analyze the lateral earth pressure on cantilever and Mechanically Stabilized Earth (MSE) walls through displacement and deformation. The research will propose two solutions for managing soil movement: MSE walls with geogrid reinforcement and inclined cantilever retaining walls. Variations in geogrid layers, reinforcement length, and inclination ratios will be explored. Additionally, replacing clayey sand backfill with sand-rubber backfill will be examined as a sustainable step to reduce soil usage. The outcomes will highlight which solutions meet allowable horizontal deflection limits.